2022
DOI: 10.1155/2022/8069858
|View full text |Cite
|
Sign up to set email alerts
|

A Two-eRNA-Based Signature Can Impact the Immune Status and Predict the Prognosis and Drug Sensitivity of Lung Adenocarcinoma

Abstract: Enhancer RNAs (eRNAs) are intergenic long noncoding RNAs (lncRNAs) participating in the development of malignant cancers via targeting cancer-associated genes and immune checkpoints. Immune infiltration of the tumor microenvironment was positively associated with overall survival (OS) in lung adenocarcinoma (LUAD). In this study, we aimed to explore the clinical significance of PCBP1-AS1 in LUAD and developed a novel prognostic signature based on two eRNAs. Our team discovered that the expression of PCBP1-AS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…It is reported that Rapamycin inhibits the growth and metastatic progression of NSCLC [41]. Besides, a strong correlation between risk scores and anticancer medication sensitivity of KIN001-102 and KIN001-135 was found in previous study [42]. PAFAH1B3 is elevated in human pan-cancer, which is correlated with greater pathology and poor prognosis, in particular for NSCLC and liver hepatocellular carcinoma (LIHC) [43].…”
Section: Discussionmentioning
confidence: 76%
“…It is reported that Rapamycin inhibits the growth and metastatic progression of NSCLC [41]. Besides, a strong correlation between risk scores and anticancer medication sensitivity of KIN001-102 and KIN001-135 was found in previous study [42]. PAFAH1B3 is elevated in human pan-cancer, which is correlated with greater pathology and poor prognosis, in particular for NSCLC and liver hepatocellular carcinoma (LIHC) [43].…”
Section: Discussionmentioning
confidence: 76%
“…So far, some related researchers have also indicated that there are also many limitations in the studies on PCBP1-AS1. In addition, there is a limited amount of highly relevant Hepatocellular carcinoma Proliferation, migration PCBP1-AS1/PRL-3-AKT/PCBP1 Oncogene Up-regulation [20,21] Vulvar squamous cell carcinoma Inhibitor of proliferation, enhance apoptosis PCBP1-AS1/TRAF5/NF-kB Inhibitor Down-regulation [24] Hodgkin lymphoma Proliferation PCBP1-AS1/mRNA Unknown Down-regulation [26] Lung adenocarcinoma Inhibitor of migration PCBP1-AS1/EMT Inhibitor Down-regulation [29][30][31] Cervical cancer Invasion, proliferation, migration PCBP1-AS1/p53/notch Oncogene Up-regulation [34][35][36] Glioma Proliferation, migration and invasion Unknown Oncogene Up-regulation [40] Colorectal cancer Inhibitor, proliferation, tolerance LncRNA-miRNA-mRNA Unknown Up-regulation…”
Section: Methylation Of Lncrna Promoter Regionmentioning
confidence: 99%
“…In order to explore the correlation between PCBP1-AS1 expression and TME for lung adenocarcinoma. Li team used CIBERSORT algorithm (A method for assessing tissue cell composition from gene expression profiles) to study the level of tumor-initiating cells subpopulation, [ 31 ] and obtained 21 types of immune cell profiles in Lung adenocarcinoma patients. Through observation, it was found that the level of monocytes, neutrophils and activated NK cells in LAUD samples was abnormal.…”
Section: Performance Of Lncrna Pcbp1-as1 In Different Cancermentioning
confidence: 99%
“…Accumulating evidence has showed that eRNAs are associated with multiple traits, characteristics, and cancers. For example, NET1 eRNA regulates the expression of neuroepithelial cell transforming 1 (NET1) oncogene to promote tumorigenesis in breast cancer (Zhang et al 2019 ) and HPSE eRNA regulates the expression of heparinase (HPSE) to promote the invasion and metastasis of cancer (Jiao et al 2018 ). The eRNA disorders can affect biological processes, including cell cycle and cancer cell growth, or change the expression of target genes (Hsieh et al 2014 ; Lam et al 2013 ; Melo et al 2013 ), adding new insights into the action mechanisms of enhancers.…”
Section: Introductionmentioning
confidence: 99%